Exploring Healthcare Workers' Experiences in Maintaining Consistent Medical Discharge Summaries within an Electronic Medical Record System: A Phenomenological Study - Abdul Malik Ritonga; Windy Andini Sitinjak; Cosmas Samuel Daeli; Sarida Surya Manurung; Jonni Sastra Manurung; Sheila Hamdah Hanum Ritonga (Benih : Journal of Midwifery, 2026)
Medical discharge summaries are essential documents in healthcare services that provide a comprehensive overview of a patient's clinical condition throughout hospitalization. The consistency of completing medical discharge summaries within an Electronic Medical Record (EMR) system plays a crucial role in ensuring documentation quality, patient safety, and the efficiency of administrative processes and health insurance claims. This study aimed to explore healthcare workers' experiences in maintaining consistent medical discharge summaries within the Electronic Medical Record system at Imelda Pekerja Indonesia General Hospital. A qualitative research design with a phenomenological approach was employed. The participants consisted of the Attending Physician (DPJP), the Head Nurse of the Emergency Department, medical record officers, Case Mix officers, and Hospital Information System (HIS) officers. Data were collected through in-depth interviews and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that the consistency of medical discharge summary documentation was influenced by three major factors: organizational support through training and socialization programs, healthcare workers' understanding of clinical documentation standards and Standard Operating Procedures (SOPs), and hospital policies supporting the implementation of Electronic Medical Records. In addition, workload, differences in perceptions regarding documentation completeness, and technical issues within the EMR system remained significant challenges affecting documentation consistency. The study concludes that strengthening healthcare workers' competencies, optimizing validation features within the Electronic Medical Record system, and implementing continuous monitoring and evaluation are necessary to improve the quality of medical documentation and hospital healthcare services.